Variasi Sapaan Pasangan Sebelum dan Sesudah Menikah di Kecamatan Jombang Kabupaten Jember: Sosiodialektologi - Sofia, Dina; Sariono, Agus; Asrumi, Asrumi (Universitas Batanghari Jambi, 2023)
The word greeting is a word that is usually used to greet the person you are talking to (second person) or replaces the name of a third person. This research is a qualitative descriptive study with the aim of describing the greeting words used by couples before and after marriage. Does someone change the greeting to their partner and how does the greeting change form. The data in this study are data in the form of greeting words used before the couple gets married and after marriage. Respondents in this study were 40 (pairs) of teachers and employees at MAN 3 Jember. The data collection technique is the interview technique. Data were analyzed and grouped according to type. The results showed that there was a change in the couple's greeting words before and after the couple was married with various variations of the greeting words.